1999
DOI: 10.1177/090591999900900109
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Donate Organs and Tissues in Vietnam

Abstract: Nearly two thirds of urban Vietnamese surveyed were willing to donate organs or tissues after death. Their willingness was related to awareness of transplantation, sex, education level, and occupation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…Previous studies have shown that people from younger age group are more motivated towards body and organ donation as compared to geriatric age group. [11][12][13] 15.73% of students were doubtful about body donation after death for they had fear in mind as to what will happen to the body after death. They had a feeling of loss of dignity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that people from younger age group are more motivated towards body and organ donation as compared to geriatric age group. [11][12][13] 15.73% of students were doubtful about body donation after death for they had fear in mind as to what will happen to the body after death. They had a feeling of loss of dignity.…”
Section: Discussionmentioning
confidence: 99%
“…In countries with active organ transplant programmes and wide acceptance criteria for transplant recipients, the need for organ grafts exceeds organ supply, even from cadaver donors. The failure of providers to give families of potential organ donors adequate information to make informed choices about organ donation and to meet their emotional needs are frequently cited reasons for non-consent (2,4,5). Many surveys indicate numerous ambiguities regarding the public's acceptance of organ donation and transplantation.…”
mentioning
confidence: 99%
“…The study findings reveal that, at the time of request, families are emotionally traumatized and decisions on transplantation may simply be more than they can handle. Dread of mutilation of the body and fear of pre-consent may adversely affect outcomes (3,4,7,8). In literature, a variety of factors were found significantly related to unwillingness to donate such as: religious and spiritual issues, cultural values and attitudes to death, the concept of brain death, separation of physician teams of donor and recipient, not knowing how and/or where to obtain donor cards, fear of burial, fear of bodily mutilation, altruism, lack of understanding of donation and lack of confidence in the professional conduct of the staff (3,(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
See 2 more Smart Citations